The person-centred approach in Aotearoa New Zealand: a critical examination of a settler psychology. (2nd January 2021) - Tudor, Keith; Rodgers, Brian
ABSTRACT: This article examines how the person-centered approach (PCA) became established in Aotearoa New Zealand, and draws parallels between how a Western psychology lands and settles and the process of colonization. Utilizing a critical methodology of both written records and oral history, the article documents the process of 'first contact' of Rogers' ideas, followed by the later 'settlement' of client- and person-centered influences through churches and ministry, marriage guidance, and relationship counseling, and the tertiary education sector. Drawing on the results of a contemporary survey, the article reflects on the limitations of the current practice of person-centered therapy, and of therapists influenced by the PCA. The article concludes with a challenge to the approach to adapt to be more culturally responsible, relevant, and responsive, particularly to the indigenous Māori people of the land.